Intervening Paths From Strain to Delinquency Among High School and Vocational School Students in China - Wang, Xin (International journal of offender therapy and comparative criminology, 2020)
Chinese education system comprises high schools and vocational school, and their differences on delinquency have seldom been investigated. From the perspective of general strain theory, the present study examined the differences among high school and vocational school students for delinquency, strain, and other explanatory variables. General strain theory delineates the effect of strain on delinquency or deviance and presents the paths from strain to delinquency or deviance through social control and social learning variables. Using a sample of 1,852 tenth-grade students in Guangzhou City, the present study tests the intervening paths from strains to deviance among high school and vocational school students. Results indicated that vocational school students have higher likelihood to be strained and delinquent, and have lower social control and higher interactions with delinquent peers. School type is a significant predictor for strain, as well as social control and delinquent peers.